Investigating Turkish teachers' views and practices on writing instruction in secondary schools: A mixed-methods study - Hasan Basri Kansızoğlu (Journal of Pedagogical Research, 2023)
This mixed-method study examines problems, practices, and suggestions associated with writing education in Turkish language courses. The study involved 96 Turkish teachers working in secondary schools. Using the responses from teachers, the results of the survey were presented on the basis of dimensions such as teachers' competencies in teaching writing, students' habits and competencies in writing, and teacher education programs' adequacy. Additionally, the study examined the additional support teachers provide to students with writing difficulties and the evidence-based practices they employ. This study found Turkish teachers participating in the study to have poor writing practices. The teaching of writing was problematic on several levels, including teacher training and student and teacher competence. Furthermore, teachers reported that secondary school writing instruction was unrelated to teacher training. It was also reported that students often lacked writing habits and had below-average writing skills. Despite the importance of evidence-based practices in effective writing instruction, teachers were deficient in providing additional support to students with writing difficulties. Last but not least, teachers' self-efficacy in evidence-based writing was not influenced by gender, educational background, school location, age, or years of teaching experience. The results point to the necessity of continuous improvement in writing education.